Notary Authority to Use Retention Right to Keep Documents Based on Custody Agreement in Legal Assurance Review - Bambang Tri Bawono (Jurnal Akta, 2021)
The purpose of this study is to determine and analyze the authority of a notary in retaining documents in the form of a power of attorney to sell and certificates that have transferred their ownership rights to other parties and to identify and analyze the position of heirs who have changed their citizenship on land ownership rights in a review of legal certainty. The approach method used in this research is sociological juridical. The results of the study stated that the storage of SHM certificate No. 2343/Salatiga by Notary WI is based on a safekeeping agreement between KT and notary WI. However, the authority to keep the certificate within a period of one year is no longer valid, considering that KT as the provider of care has changed its citizenship to become a citizen of the Netherlands. This refers to article 21 paragraph (3) of Act No. 5 of 1960 concerning Basic Agrarian Regulations. With the enactment of such provisions, the Notary WI within one year since the inheritance no longer has the right to keep the land certificate SHM No. 2343/Salatiga, considering that KT as the power of attorney no longer has rights to the land.